English Teachers’ Understanding of Language Assessment - Wijayanti, Dina Novita (Institut Agama Islam Negeri Kudus, 2019)
In reality, most of the teachers assess the students’ works only by using test. Ideally, as teachers whose job assess the students’ works, they must understand and apply the concept of measurement include testing, assessment, examination, and evaluation. In fact, we sometimes find phenomena where the teachers get confused to differ among them. Because of the reasons above, the researcher is interested in describing how far the English teachers understand about language assessment and how they assess and interpret the students’ work. The research is conducted in the form of qualitative. The subjects of the study are 2 English teachers from SMA 1 Kudus and 2 English teachers from SMP 3 Bae Kudus. The findings showed that only 25% teachers understood language assessment. The others found difficulties in differentiating and applying measurement concept. So, it can be inferred that teachers’ understanding still needed improvement.